Association of MTHFR C677T Polymorphism With Antipsychotic-Induced Change of Weight and Metabolism Index - Su, Yi; Yan, Hao; Guo, Liangkun; Lu, Tianlan; , CAPOC; Zhang, Dai; Yue, Weihua (Frontiers in Psychiatry, 2021)
Though antipsychotic medication contributed to the improvement of psychotic symptoms and reduced relapse, it induced weight gain and metabolic syndrome during antipsychotic medications treatment that were seriously concerned. To investigate the association of methylenetetrahydrofolate reductase (MTHFR) gene C677T (rs1801133) polymorphism with antipsychotic-induced weight gain and metabolism parameters change, we employed 1,868 patients with schizophrenia in this study and randomly allocate them to 7 antipsychotic medication treatment groups. All patients received antipsychotics monotherapy and were followed up for 6 weeks. Height, body weight and metabolic parameters of the patients were measured at baseline, 2, 4 and 6 weeks after antipsychotic treatment. We genotyped blood DNA from patients for MTHFR C677T polymorphisms and performed quantitative analyses using analysis of variance (ANOVA) and the analysis of covariance (ANCOVA) among 3 genotype groups. We found a predominant association between MTHFR C677T and body weight mass index (BMI) change after 6-week risperidone treatment. After 6-week treatment of risperidone, the BMI change rate (%) of MTHFR C677 carriers was significantly higher than that of MTHFR TT genotype carriers [CC (2.81±6.77)%, CT (3.79±5.22)%, TT (1.42±3.53)%, F = 4.749, P = 0.009]. Some of the abnormal metabolic parameters were found to be associated with the MTHFR 677T, including higher levels of low-density lipoprotein and waist circumference. Validation was performed in an independent cohort, consisting of 252 patients with schizophrenia treated with 3 atypical antipsychotic drugs. Overall, the MTHFR C677 was associated with high risk of antipsychotic-induced weight gain and metabolism abnormalities.